LONG-TERM PROGNOSIS AND MODES OF DEATH IN HEART FAILURE PATIENTS WITH REDUCED VERSUS PRESERVED LEFT VENTRICULAR SYSTOLIC FUNCTION - Mavrea, Adelina; Korpos-Gyalai, I.; Citu, Ioana; Ancusa, Oana; Bordejevic, Aurora; Tomescu, Mirela C. (European Scientific Journal, ESJ, 2014)
Background: There are conflicting reports regarding the prognosis of heart failure patients with preserved (HFPSF) comparative to reduced systolic left ventricular function (HFRSF). We evaluated the clinical characteristics, mortality rates and modes of death in 309 consecutive symptomatic heart failure patients. In 133(56%) patients LVEF was <50% (HFRSF), and in 133 (44%), LVEF was ≥50% (HFPSF). Methods: Three hundred nine consecutive patients hospitalized between January 1, 2009 and January 1, 2010 (176 men and 133 women, mean age 64.3 years) were followed up for a mean period of 23±14 months. The severity of symptoms at admission was assessed by NYHA classification. 196 patients were in NYHA class I-II, and 113 in III–IV. All patients underwent chest X-ray, echocardiogram, and a 6-minute walking test. We compared the clinical profiles, mortality rates and modes of death. Results: More than a third (44%) of the patients had preserved systolic LVEF based on echocardiography. Compared to the HFPSF group, HFRSF patients were predominantly younger males with ischemic aetiology and less cardiovascular comorbidities such as obesity, hypertension, diabetes mellitus and atrial fibrillation. During a mean follow-up period of 1.9 years, 22 (7.1%) patients died: 14 of cardiac causes and 8 of non-cardiac causes (4 of respiratory causes, 2 of stroke, 1 of major bleeding and 1 of cancer). Overall mortality was similar between the two groups: 8 (6%) in HFPSF patients and 14 (7.9%) in HFRSF patients (p=0.67). HFRSF patients had higher death rates due to pump failure compared to the HFPSF group [ 5/14(36%) vs. 1/8(12%) patients, p=0.5]. Non-cardiac deaths were more frequent in HFPSF group [4/8 (50%) patients vs. 4/14(28%) patients, respectively, p=0.5]. The prevalence of arrhythmic death was similar in the two groups [5/14(36%) vs.3/8(37%) patients, p=0.6]. With Cox stepwise regression analysis for survival, the independent predictors for mortality were age, gender, ischemic etiology of heart failure and renal impairment. Conclusions: Although the characteristics of HFPSF and SHF patients are different, the mortality rates were similar in our study. The mode of death was different among the two groups of patients, as pump failure death rate was higher in patients with LVEF <50%, while non-cardiac death was higher in heart failure patients with preserved systolic function. The differences were not statistically significant. A high NYHA class at admission, age over 65, male gender and renal impairment were related to a worse prognosis.